Tb3+ ion green emissions by the energy transfer from ZnO nanocrystals embedded in SiO2 film - Tang, Dennis Khean Kee (2018)
The direct wide band gap of 3.37eV of Zinc Oxide (ZnO) makes it a material that can be used in electronics and optoelectronic devices. Energy transfer from Zinc Oxide nanocrystals (ZnO-nc) embedded in Silicon dioxide (SiO2) matrix has been proven to be able to excite Rare earth (RE) ions like Europium (Eu3+) and Terbium (Tb3+) to produce visible lights of different colours.